Da Atenas à Jamaica brasileira: imaginários sobre São Luís na mídia maranhense - Santos, Samuel Pereira dos [UNESP] (2003)
Approaching about a study in the cut of the speech analysis from French line that sees the text (verbal and non-verbal) interlacing of voices that stabilize according to the ideology for communicating, this present study makes a press cutting from printed media that constitute the epithets of Brazilian Athenas and Brazilian Jamaica the city of São Luis of Maranhão. This interlacing is catched in the materiality of the texts from the newspapers The Imparcial and The State of Maranhão, that propoce the effects of sence for modelling according to the culture of the folk's identitity, promoting the imposbility of the individual gets out from the game or the sign order or from the ideology. Through from remission to the collective symbole, the media promove an absolute unit from the enuciations that circle in the vehicles and introduce to the collectivity the identitity speeches that will feed the social imaginary of the folk from Maranhão the way of Athenas to the Brazilian Jamaica